Median Statistics Estimate of the Distance to the Galactic Center. (11th January 2018) - Camarillo, Tia; Mathur, Varun; Mitchell, Tyler; Ratra, Bharat
Abstract: We show that error distributions of a compilation of 28 recent independent measurements of the distance from the Sun to the Galactic center, R 0, are wider than a standard Gaussian and best fit by an n = 4 Student's t probability density function. Given this non-Gaussianity, the results of our median statistics analysis, summarized as R 0 = 8.0 ± 0.3 kpc (2 σ error), probably provides the most reliable estimate of R 0 .